2016
DOI: 10.1093/asj/sjw004
|View full text |Cite
|
Sign up to set email alerts
|

Autologous Fat Grafting: The Science Behind the Surgery

Abstract: An invaluable part of the plastic surgeon's technical arsenal for soft tissue contouring, fat grafting continues to be plagued by unpredictable outcomes, resulting in either reoperation and/or patient dissatisfaction. Thus, extensive research has been conducted into the effects of adipose tissue procurement, processing, and placement on fat graft quality at both the cellular level and in terms of overall volume retention. Herein, we present an overview of the vast body of literature in these areas, with additi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
81
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(83 citation statements)
references
References 91 publications
(87 reference statements)
1
81
0
1
Order By: Relevance
“…15 In addition, the absence of a standardized, objective, non-invasive method to evaluate the outcomes of fat transplant makes it difficult to compare results obtained following different procedures or the effects of similar methods on different patients. 16,17 .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…15 In addition, the absence of a standardized, objective, non-invasive method to evaluate the outcomes of fat transplant makes it difficult to compare results obtained following different procedures or the effects of similar methods on different patients. 16,17 .…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Fat grafting has been regarded as a promising biomaterial for soft‐tissue reconstruction, because it is readily available; easily obtainable, with low donor‐site morbidity; repeatable; inexpensive; versatile; and biocompatible . However, although fat graft provides good results in the early period, it may disappoint the patient and surgeon in the long term because of its reported resorption rate of 10%–90% . Strategies to reduce the reabsorbed proportion of fat have evolved, and they focus on the surgical technique, donor‐site selection, supplementation of stromal vascular fraction or ASCs, and the addition of growth factors.…”
Section: Introductionmentioning
confidence: 99%
“…Tan et al have recently shown that the indolamine hormone melatonin promotes survival of fat grafts via reducing inflammation . However, loss of transplanted graft is the result of hypoxia and a lack of nutrients because of ischemia when the implanted tissue does not become fully vascularized to support the metabolic needs of the tissue in the required timeframe. Reducing fat‐graft desorption is still an area that needs further improvement, we may consider to find more efficient agent to enhance survival of the substitute graft under ischemia condition.…”
Section: Introductionmentioning
confidence: 99%
“…The most problematic issue is that this decline over time is not foreseeable because it depends on several variables. These include the choice of donor site infiltration, the harvesting technique, the diameter of the cannula, the magnitude of negative pressure utilized, the processing method of the harvested tissue, the reinjection procedure, the content in ADSCs, and the amount and integrity of mature adipocytes …”
mentioning
confidence: 99%
“…These include the choice of donor site infiltration, the harvesting technique, the diameter of the cannula, the magnitude of negative pressure utilized, the processing method of the harvested tissue, the reinjection procedure, the content in ADSCs, and the amount and integrity of mature adipocytes. 1 The processing of the collected material is one of the most important topics to be investigated. 10 This issue is still under debate and a unique agreement has not been reached yet.…”
mentioning
confidence: 99%